A Matter of Size: Flipping Library Instruction in Various Engineering Classrooms. - Tasha Maddison (Issues in Science and Technology Librarianship)
This case study explores the use of flipped teaching in three different undergraduate engineering courses, discussing the advantages and disadvantages of class size and how it affects the delivery of information literacy instruction as observed through student engagement and the perceived helpfulness of the instruction. A flipped classroom was used in three separate engineering design classes during the 2014-15 academic school calendar. Two of these classes were offered in a computer lab to less than 30 students (one class was divided into sections for ease of instructional delivery) and one was offered to a large class in a lecture format without the availability of computers for each student. The flipped components relied on online video tutorials that were posted on YouTube and then embedded in the library guides for the discipline. This paper provides the results from an analysis of page views alongside usage statistics from YouTube. Both of these sources of information along with post-test results provided useful data in determining the effectiveness of flipped teaching in both a large lecture format and a smaller computer lab setting. The highest engagement scores were seen from the classes taught in a computer lab. [ABSTRACT FROM AUTHOR]